Opportunities and threats for agrifood firms. The case of wineries applying Rasch analysis - Vanessa Yanes-Estévez; Ana María García-Pérez (Wine Economics and Policy)
This article identifies the opportunities and threats perceived by winery managers in the new general environment after to Covid-19. The sample comprised 66 wineries located in the Canary Islands (Spain), whose managers answered a questionnaire. This region has a long wine tradition and it has been re-developed and reborn via quality since the 1990s. Rasch analysis and its Differential Item Functioning (DIF) were used to process the information as novel competitive analysis tools. The main opportunities found are the islands’ climate, in addition to the social values and lifestyle. The main threats are the unemployment rate and, with less much negative influence, all the restrictions and regulations derived from Covid-19. The only difference considering age and size of wineries is the influence of the climate: wineries that have been active for more than 30 years perceive it even as a greater opportunity, than the youngest ones. The results are useful both for existing wineries and for potential entrepreneurs who want to open a business in this sector to effectively focus their efforts on the existing opportunities.